A Smart Water Tank for Control and Monitoring Based on IoT Technology - Parenreng, Jumadi M.; Lamada, Mustari S; Baktiar, Nurul Isra Humaira; Adibah, Fhatiah; Risal, Andi Akram Nur (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
This research is a Research and Development study, developing a tool to overcome water wastage and monitor water conditions in the tandon. This tool uses water flow, pH, and turbidity sensors connected to a telegram bot and LCD. This research applies a prototype model that includes problem identification, needs analysis, literature study, tool design, program coding, tool installation, and tool testing. Functional testing of the tool shows that all components function correctly. From the test results obtained comparison test of measuring water volume entering using the water flow in the sensor and measuring cup results in an MPE of 0.067, while measuring water volume exiting using the water flow out the sensor and measuring cup results in an MPE of 0.048. Comparison test of measuring pH using a pH sensor and pH meter results in an MPE of 0.067. Measuring water turbidity level using a turbidity sensor shows the ability of the sensor to measure turbidity on various water samples. The telegram bot, LCD monitoring, and automatic water pump systems work well.